Analysis of Coxiella burnetii genomes in context of epidemic Q fever - S. N. Shpynov; N. V. Rudakov; S. Yu. Zelikman; D. V. Trankvilevskiy (Фундаментальная и клиническая медицина)
Q fever is a zoonotic infection caused by Coxiella burnetii. Infected goats, sheep and cattle, materials of animal origin, meat and dairy products are the main sources of C. burnetii for humans. Dust C. burnetii infection is of particular importance due to the high resistance of this pathogen. C. burnetii is considered as a biological weapon and its use as an aerosol causes acute diseases with further disability. Chronic C. burnetii infection can cause endocarditis, leading to a chronic fatigue syndrome or even death. In the Netherlands, a pronounced increase in the incidence of Q fever in humans was detected from 2007 to 2010 (≥ 4,000 acute cases), mostly associated with goat farms. Analysis of 10 C. burnetii genomes allowed molecular epidemiology screening of coding and non-coding structures for studding the possible origin of the outbreak strains. Strains Z3055 (sheep placenta, Germany) and NL3262 (goat placenta, Netherlands) are the most closely related (84.9% homologous sequence). Formal order analysis distinguished 6 groups of C. burnetii strains. Adaptation to a new host emerged as a driving force for the reorganization of C. burnetii genome. The largest epidemic of Q fever could occur because of an inadequate veterinary supervision that led to the epizootic and further epidemic in the farmers producing the goat cheese. The transition of the «sheep» (Z3055-like) strain to the «goat» (NL3262) strains, characterised by a change of the host during the epizootic, could signifcantly contribute to the severity of that Q fever epidemic.